PEMAKAIAN DOKTRIN AL-MASALIH AL-MURSALAH DALAM HUKUM AL-FARA’ID: Application of Doctrine of al-Masalih al-Mursalah in Fara’id - Sulong, Jasni; Ismail, Faisal Husen (Jurnal Syariah, 2011)
Al-Masalih al-Mursalah was one of the sources in Islamic jurisprudence which does not reach unanimous acceptance among scholars. This principle was established based on the importance and beneficial impact towards people, in which all goodness, benefit, welfare and those that could guaranteed the better condition towards mankind will be accepted as the basis for law maker. Furthermore, these principle neither be found directly in the Qur‘an nor in the Traditions. Among scholars, it cause variance justification in deciding which is the best and utmost for people based on these differences, including in inheritance matters. Hence, the study aimed to identify the concept of al-maslahah and its application in dividing inheritance among heirs. The study found that there are implications of these variances among Muslim scholars in determining what al-maslahah is for heirs. Nevertheless, the study also found that the benefit of heirs always the essential part of scholar’s thought such as giving alternative space based on the situation and the right of heirs which could benefit them through bequeath and gift mechanism. It was obvious that the guarantee of maslahah unlimited in the division of estate through inherintance only, but far beyond.